Fiscal Policy in Islamic History: from Baitul Mal Management to the Tax System - Wardiman, Dadi; Janwari, Yadi; Hasanuddin, Muhammad (CV. Strata Persada Academia, 2025)
Fiscal policy is a crucial aspect of economic management in a nation. In Islamic history, fiscal policy has functioned not only as a revenue collection mechanism but also as an instrument for achieving social and economic welfare. This study explores the evolution of Islamic fiscal policy, from the management of Baitul Mal to the development of modern taxation systems. This study employs a qualitative approach using heuristic and historiographical methods, analyzing secondary literature sources from various historical periods. The findings indicate that Islamic fiscal policy has historically aimed to achieve economic balance and social justice. Baitul Mal functioned as a wealth redistribution tool, while taxation systems were developed to finance public infrastructure. Despite challenges such as corruption and unequal resource distribution, the fundamental principles of Islamic fiscal policy remain relevant in the modern economic context. Therefore, this study recommends the implementation of transparency, accountability, and fiscal balance as guiding principles for contemporary economic policies to achieve stability and sustainable development.